Solvolysis of Bituminous Coal in Coal- and Petroleum-Derived Commercial Solvents - Kuznetsov, Peter N. (ACS Omega, 2020)
[Image: see text] The solvolytic conversion of softening bituminous coal at 380 °C in solvents derived from the commercial hydrocarbon byproducts and residues from coal and petroleum processing was studied. Hydrogen-donor tetrahydronaphthalene (THN) and nondonor 1-methylnaphthalene (MN) were also used for comparison. The high-boiling solvents of different chemical classes (highly aromatic coal tar, its anthracene fraction, and low-aromatic heavy gas oil of catalytic cracking of the oil residue) and the H-donor THN solvent were found to exhibit high efficiency for coal conversion into quinoline-soluble products. The chemical and molecular compositions of coal, solvents, and dissolved products were characterized in detail by different techniques, including chemical analysis, group analysis, infrared Fourier transform (IRFT) spectroscopy, X-ray diffraction (XRD), liquid chromatography, and thermal analysis to reveal the chemical transformations of the coal–solvent mixture during the dissolution reaction. The solvolysis of coal in the liquid phase of both highly aromatic and low-aromatic solvents was found to involve selective depolymerization of polymer-like coal via breaking of weak linkages between the aromatic units, resulting in the formation of soluble pitchlike products. The effective dissolution of coal in the H-donor THN solvent resulted probably from a combination of the nonselective thermal fragmentation of the coal structure to smaller radical intermediates and their stabilization by hydrogen from THN, producing mainly tar and a few gases. The low-boiling solvents of both predominantly aromatic and aliphatic classes (gas oils from naphtha pyrolysis and delayed coking of the petroleum residue) and MN exhibited poor efficiency for coal dissolution. The concentrations of carcinogenic benzo(a)pyrene (BaP) in the solvents used and in the toluene fractions of the resulting extracts were analyzed. The remarkable result was that coal extracts, compared to solvents, contained much less BaP, probably due to its conversion with coal and/or solvent molecules during coal dissolution.